Predicting Responses to Psychedelics: A Prospective Study - Haijen, Eline C. H. M.; Kaelen, Mendel; Roseman, Leor; Timmermann, Christopher; Kettner, Hannes; Russ, Suzanne; Nutt, David; Daws, Richard E.; Hampshire, Adam D. G.; Lorenz, Romy; Carhart-Harris, Robin L. (Frontiers in Pharmacology, 2018)
Responses to psychedelics are notoriously difficult to predict, yet significant work is currently underway to assess their therapeutic potential and the level of interest in psychedelics among the general public appears to be increasing. We aimed to collect prospective data in order to improve our ability to predict acute- and longer-term responses to psychedelics. Individuals who planned to take a psychedelic through their own initiative participated in an online survey (www.psychedelicsurvey.com). Traits and variables relating to set, setting and the acute psychedelic experience were measured at five different time points before and after the experience. Principle component and regression methods were used to analyse the data. Sample sizes for the five time points were N = 654, N = 535, N = 379, N = 315, and N = 212 respectively. Psychological well-being was increased 2 weeks after a psychedelic experience and remained at this level after 4 weeks. Higher ratings of a “mystical-type experience” had a positive effect on the change in well-being after a psychedelic experience, whereas the other acute psychedelic experience measures, i.e., “challenging experience” and “visual effects”, did not influence the change in well-being after the psychedelic experience. Having “clear intentions” for the experience was conducive to mystical-type experiences. Having a positive “set” as well as having the experience with intentions related to “recreation” were both found to decrease the likelihood of having a challenging experience. The baseline trait “absorption” and higher drug doses promoted all aspects of the acute experience, i.e., mystical-type and challenging experiences, as well as visual effects. When comparing the relative contribution of different types of variables in explaining the variance in the change in well-being, it seemed that baseline trait variables had the strongest effect on the change in well-being after a psychedelic experience. These results confirm the importance of extra-pharmacological factors in determining responses to a psychedelic. We view this study as an early step towards the development of empirical guidelines that can evolve and improve iteratively with the ultimate purpose of guiding crucial clinical decisions about whether, when, where and how to dose with a psychedelic, thus helping to mitigate risks while maximizing potential benefits in an evidence-based manner.